Factors Affecting Financial Distress with Managerial Ownership as a Moderating Variable - Hana Jenifer; Muhyarsyah Muhyarsyah (Budapest International Research and Critics University, 2023)
This research examines the impact of leverage, liquidity, and sales growth on financial distress (FD) with managerial ownership as a moderating variable. A total of 138 consumer cyclicals companies registered on the Indonesia Stock Exchange (IDX) for 2020 – 2021 are included as a population in this study. Purposive sampling was utilized to choose 102 companies for this research. This analysis was performed using logistic regression and moderating regression analysis (MRA). The findings showed that leverage had an impact on FD, while liquidity and sales growth had no effect on FD. leverage, liquidity, and sales growth simultaneously affect FD. Managerial ownership not able moderates the impact of leverage, liquidity, and sales growth on FD.